A multi-country evaluation of Neisseria meningitidis serogroup B factor H-binding proteins and implications for vaccine coverage in different age groups - Hoiseth, Susan K; Murphy, Ellen; Andrew, Lubomira; Vogel, Ulrich; Frosch, Matthias; Hellenbrand, Wiebke; Abad, Raquel; Vazquez, Julio A; Borrow, Ray; Findlow, Jamie; Taha, Muhamed-Kheir; Deghmane, Ala-Eddine; et al. (The Pediatric infectious disease journal, 2013)
BACKGROUND: Recombinant vaccines containing factor H-binding protein (fHBP) have been developed for the purpose of protection from invasive meningococcal serogroup B disease. Neisseria meningitidis fHBP sequences can be divided into 2 genetically and immunologically distinct subfamilies (A and B); thus, cross protection is conferred within but not between subfamilies. A comprehensive understanding of fHBP epidemiology is required to accurately assess the potential vaccine impact when considering different vaccination implementation strategies. METHODS: Systematically collected invasive meningococcal serogroup B isolates from England, Wales, Northern Ireland, the United States, Norway, France and the Czech Republic were previously characterized for fHBP sequence. This study expanded the evaluation with additional meningococcal serogroup B disease isolates from Spain (n = 346) and Germany (n = 205). This expanded set (n = 1841), collected over a 6-year period (2001 to 2006), was evaluated for fHBP sequence and fHBP subfamily relative to patient age. RESULTS: All 1841 isolates contained fhbp. fHBP sequences from Spain and Germany fell within the previously described subfamilies, with 69% of isolates belonging to subfamily B and 31% to subfamily A; prevalent sequence variants were also similar. Stratification of data by age indicated that disease in infants <1 year of age was caused by a significantly higher proportion of isolates with fHBP subfamily A variants than that seen in adolescents and young adults 11-25 years (47.7% versus 19.5%, P < 0.0001, respectively). CONCLUSIONS: These observations highlight a difference in epidemiology of fHBP subfamilies in different age groups, with fHBP subfamily A strains causing more disease in vulnerable populations, such as infants, than in adolescents.
Keywords: dospělí; Europe; Infant; antigeny bakteriální; dítě; předškolní dítě; Age Factors; Adult; bakteriální proteiny; Adolescent; Bacterial Proteins; meningokokové infekce; Meningococcal Vaccines; věkové faktory; lidé; Evropa; Meningococcal Infections; meningokokové vakcíny; Spojené státy americké; kojenec; Aged; Neisseria meningitidis; Child, Preschool; Antigens, Bacterial; United States; lidé středního věku; Child; senioři; Middle Aged; mladiství; Humans